A Cautionary Tale: Some Insights Regarding Judicial Activism from the National Experience - DE VISSER, Maartje (Institutional Knowledge at Singapore Management University, 2013)
Courts, whether national or European, are sometimes subject to charges of judicial activism. Adopting a comparative perspective, this contribution charts the ways in which constitutional courts in the Member States have sought to mitigate or pre-empt charges of activism. The primary purpose is to identify attractive solutions or lessons the ECJ may draw from dealing with this perception of judicial activism. It is important at the outset to be clear about what is meant by ‘judicial activism’. Judicial activism is often used as a slogan to communicate dislike or disagreement with a particular judgment or line of case law. While such a subjective approach has rightly been criticized, we should acknowledge that politicians, the media and the public regularly employ the term in this derogatory sense. As such, judicial activism is closely connected to the way in which these actors perceive the legitimacy of the court and its judgments, whereby judicial activism is commonly seen as a legitimacy-eroding factor.